Aberrant methylation of nucleotide excision repair genes is associated with chronic arsenic poisoning - Zhang, Aihua; Li, Huiyao; Xiao, Yun; Chen, Liping; Zhu, Xiaonian; Li, Jun; Ma, Lu; Pan, Xueli; Chen, Wen; He, Zhini (Biomarkers, 2017)
Objective: To define whether aberrant methylation of DNA repair genes is associated with chronic arsenic poisoning. Methods: Hundred and two endemic arsenicosis patients and 36 healthy subjects were recruited. Methylight and bisulfite sequencing (BSP) assays were used to examine the methylation status of ERCC1, ERCC2 and XPC genes in peripheral blood lymphocytes (PBLs) and skin lesions of arsenicosis patients and NaAsO 2 -treated HaCaT cells. Results: Hypermethylation of ERCC1 and ERCC2 and suppressed gene expression were found in PBLs and skin lesions of arsenicosis patients and was correlated with the level of arsenic exposure. Particularly, the expression of ERCC1 and ERCC2 was associated with the severity of skin lesions. In vitro studies revealed an induction of ERCC2 hypermethylation and decreased mRNA expression in response to NaAsO 2 treatment. Conclusion: Hypermethylation of ERCC1 and ERCC2 and concomitant suppression of gene expression might be served as the epigenetic marks associated with arsenic exposure and adverse health effects.